2016 design salary survey : tools, trends, titles, what pays (and what doesn't) for design professionals - King, John; Magoulas, Roger (O'Reilly Media, 2016)
This past autumn, O'Reilly Media for the first time conducted an anonymous online survey of salaries of designers, UX/UI specialists, and others in the design space. This in-depth report presents complete survey results which demonstrate how variables such as job title, location, use of specific tools, and the types of tasks performed affect salary and other compensation. The survey attracted more than 300 designers, managers, and directors from 25 countries. Most of them work onweb and mobile products or connected devices in a wide variety of industries. Respondents' median salaries have been sorted according to: Work location (country or US region), age, gender, and education Job title, such as director, manager, consultant, developer, analyst, and designer Company size, products and services produced, team size, and design processes used Professionals they work with most, including programmers, other designers, and product managers A range of tasks, including user research, usability testing, information architecture, UI design, prototyping, and project management Tools used most often, from Dropbox, Slack, and GitHub to Adobe Illustrator, Sketch, and InVision, to Google Analytics and HTML/CSS Curious how you would do in a different location, or how different skills and responsibilities might affect your salary? Download this free report to gain insight from these potentially career-changing findings, and learn how to plug your own information into the survey's linear model. To stay up to date on this research, your participation is critical. The survey is now open for the 2017 report, and if you can spare just 10 minutes of your time, we encourage you to go to http://www.oreilly.com/design/2017-​design-salary-survey.html .